Multiproxy Holocene Fire Records From the Tropical Savannas of Northern Cape York Peninsula, Queensland, Australia - Rehn, Emma; Rowe, Cassandra; Ulm, Sean; Gadd, Patricia; Zawadzki, Atun; Jacobsen, Geraldine; Woodward, Craig; Bird, Michael (Frontiers in Ecology and Evolution, 2021)
Palaeoecology has demonstrated potential to inform current and future land management by providing long-term baselines for fire regimes, over thousands of years covering past periods of lower/higher rainfall and temperatures. To extend this potential, more work is required for methodological innovation able to generate nuanced, relevant and clearly interpretable results. This paper presents records from Cape York Peninsula, Queensland, Australia, as a case study where fire management is an important but socially complex modern management issue, and where palaeofire records are limited. Two new multiproxy palaeofire records are presented from Sanamere Lagoon (8150-6600 cal BP) and Big Willum Swamp (3900 cal BP to present). These records combine existing methods to investigate fire occurrence, vegetation types, and relative fire intensity. Results presented here demonstrate a diversity of fire histories at different sites across Cape York Peninsula, highlighting the need for finer scale palaeofire research. Future fire management planning on Cape York Peninsula must take into account the thousands of years of active Indigenous management and this understanding can be further informed by palaeoecological research.